Embedded Internet design - Williams, Al 1963- (McGraw-Hill, 2003)
Exploring how to make microcontroller systems that are Internet-active, this book covers both Java-enabled modules and stand-alone microcontroller designs. It is useful as an introduction to web technology basics for hardware designers.